Relationship between total 25(OH)D and interleukin-2 contents in preterm conversion patients - Sanjaya, I Nyoman Hariyasa; Mulyana, Ryan Saktika; Kamajaya, I Gusti Ngurah Agung Trisnu (Indonesian Journal of Perinatology, 2024)
The most essential nutrient for pregnant women is vitamin D. A lack of vitamin D can cause preterm labor and other issues like low birth weight, preeclampsia, and issues with the baby's bones. According to some research, there is no safe top level and a 75–80 nmol/L range. According to additional studies, an ideal range is between 75 and 110 nmol/L and a daily dosage of 1800 to 4000 IU of vitamin D3. In both early and late pregnancies, women with sufficient vitamin D levels (at least 30 ng/mL) exhibited a significant decrease in the incidence of preeclampsia. It is also known that vitamin D modulates the immune system in several ways. T-cell proliferation can be suppressed, and pro-inflammatory cytokines, including IL-2, IFN-, and IL-17, can be produced less frequently when vitamin D is present. A lack of vitamin D may lead to a rise in cytokines that promote inflammation, such as IL-2. This paper will, therefore, examine the relationship between vitamin D, IL-2 levels, and the risk of premature labor.